Diffusion of culture in time of globalization - Samoylov, O.F. (Проблеми міжнародних відносин, 2012)
This article deals with the peculiarities of contemporary globalization processes, influence of globalization on the development of modern culture. The influence of globalization of culture on international relations is also studied.